Pigmented epithelioid melanocytoma: a pediatric case. - El Bouhmadi, A.; El Fatoiki, F.; Diouri, M.; Hali, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2025)
Pigmented epithelioid melanocytoma (PEM) is a rare, low-grade melanocytic tumor that primarily affects children and young adults. This report details a case of an 8-year-old girl presenting with a pigmented scalp lesion. Clinical examination revealed a black nodular tumor, confirmed through dermoscopy and histopathology to be PEM, characterized by large, pigmented melanocytes with epithelioid or spindle-shaped morphology. Immunohistochemistry showed positive staining for Melan-A and HMB-45. The lesion was surgically excised with no lymph node involvement or metastasis on follow-up. Despite potential regional lymph node metastasis, PEM typically has a benign clinical course, and complete surgical excision remains the preferred treatment.